Respuesta :

Answer:

=[tex]\frac{1}{6}[/tex]

Step-by-step explanation:

3+4=9+3

3+4−4=9+3−4

Answer:

x = 1/6

Step-by-step explanation:

Subtract 4 from both sides of the equation.

3x + 4 - 4 = 9x + 3 - 4

Simplify, subtract the numbers.

3x = 9x - 1

Subtract 9x from both sides of the equation.

3x - 9x = 9x - 1 - 9x

Simplify, combine like terms.

-6x = -1

Divide both sides of the equation by the same term.

-6x/-6 = -1/-6

Simplify, cancel terms that are in both the numerator and denominator, and divide the numbers.

x = 1/6